Combination of alpha-synuclein immunotherapy with anti-inflammatory treatment in a transgenic mouse model of multiple system atrophy - Valera, Elvira (Acta Neuropathol Commun, 2017)
Multiple system atrophy (MSA) is a fatal neurodegenerative disorder characterized by the pathological accumulation of alpha-synuclein (α-syn) in oligodendrocytes. Therapeutic efforts to stop or delay the progression of MSA have yielded suboptimal results in clinical trials, and there are no efficient treatments currently available for MSA patients. We hypothesize that combining therapies targeting different aspects of the disease may lead to better clinical outcomes. To test this hypothesis, we combined the use of a single-chain antibody targeting α-syn modified for improved central nervous system penetration (CD5-D5) with an unconventional anti-inflammatory treatment (lenalidomide) in the myelin basic protein (MBP)-α-syn transgenic mouse model of MSA. While the use of either CD5-D5 or lenalidomide alone had positive effects on neuroinflammation and/or α-syn accumulation in this mouse model of MSA, the combination of both approaches yielded better results than each single treatment. The combined treatment reduced astrogliosis, microgliosis, soluble and aggregated α-syn levels, and partially improved behavioral deficits in MBP-α-syn transgenic mice. These effects were associated with an activation of the Akt signaling pathway, which may mediate cytoprotective effects downstream tumor necrosis factor alpha (TNFα). These results suggest that a strategic combination of treatments may improve the therapeutic outcome in trials for MSA and related neurodegenerative disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40478-016-0409-1) contains supplementary material, which is available to authorized users.